2016
DOI: 10.1007/s00259-016-3418-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between partial-volume corrected SUVmax and Oncotype DX recurrence score in early-stage, ER-positive/HER2-negative invasive breast cancer

Abstract: High PVC-SUVmax on (18)F-FDG PET/CT was significantly associated with an intermediate-to-high Oncotype DX RS. PVC metabolic parameters on (18)F-FDG PET/CT can be used to predict the Oncotype DX RS in patients with early-stage, ER-positive/HER2-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…More recently, reports regarding the usefulness of volume-based quantitative parameters (SUVmax, MTV, TLG) for predicting prognosis using major receptor types have been presented. A study of ER+/HER2-cancer patients showed primary tumor MTV as an independent factor for predicting recurrence [19], while primary tumor SUVmax was demonstrated to be an independent factor in another report [20]. Also, primary tumor SUVmax was shown to be an independent factor with influence on recurrence in triple-negative cancer patients [21].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, reports regarding the usefulness of volume-based quantitative parameters (SUVmax, MTV, TLG) for predicting prognosis using major receptor types have been presented. A study of ER+/HER2-cancer patients showed primary tumor MTV as an independent factor for predicting recurrence [19], while primary tumor SUVmax was demonstrated to be an independent factor in another report [20]. Also, primary tumor SUVmax was shown to be an independent factor with influence on recurrence in triple-negative cancer patients [21].…”
Section: Discussionmentioning
confidence: 95%
“…Although previous studies of stage operable breast cancer patients only evaluated primary tumor quantitative FDG-PET/CT values as imaging biomarkers [2,[4][5][6][18][19][20][21], cases with a lower primary tumor SUVmax value as compared to that for nodal SUVmax are commonly encountered in clinical situations. In the present cohort as well, it was observed in 10.2-30.9% and we defined that as maximum SUVmax, which is considered to be a strong point of this report.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al did not include BC with tumour size < 8 mm. Even with this precaution, when SUV values were not corrected for partial volume effect, results were not significant [7].…”
mentioning
confidence: 94%
“…Association between high baseline tumour SUV max measured by 18 FDG-PET/CT and some poor prognostic factors such as high tumor grade is well known [5,6]. In this issue of the European Journal of Nuclear Medicine and Molecular Imaging, Lee and colleagues report on a potential new role of 18 FDG-PET/CT in early stage BC patients: prediction of the results of the Oncotype DX RS [7]. In a retrospective analysis of 38 patients with small (only one patient had a tumor > 3 cm) and nodenegative breast cancer, partial-volume corrected tumour SUV max (PVC-SUV max ) had significant association with the Oncotype DX RS; a PVC-SUV max higher than a cutoff value of 4.96 predicted intermediate-to-high RS.…”
mentioning
confidence: 99%
See 1 more Smart Citation